Optimum Site Selection Using GIS Analysis Techniques (University of Khartoum Engineering Journal, 2022)
The application of geographic information system (GIS) in optimum site selection for investment projects and proposed projects will give solutions to most of the problems hindering the investment and customers regarding the selection of optimum sites for projects in accordance with feasibility studies and minimum costs. Moreover, GIS helps in setting plans for future needs. The core of this study is a computerized model based on the technology of geographic information systems. The types of software used were AutoCAD version 2002 for vectorization; editing and transformation; ArcInfo for Topology and retopology; and ArcView GIS 3.2a for adding attribute database and performing the spatial analysis. In this model, two study areas were selected: an urban area (see figure 1.1) and a rural area (see figure 1.2) from two topographic maps provided by Sudan Survey department at a scale of 1/100000. The urban area includes an extensive area of greater Khartoum map, Khartoum province and Khartoum north province (Bahri). The urban study area equals (1315.364) km2. The rural area includes many villages of Jabel Awlia province. This area equals (1453.522)km2. The method of analysis used to select the ideal site is the intersection method. This method is like the intersection method of Sets theory in linear algebra.